2007
DOI: 10.3174/ajnr.a0752
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Aneurysm Volume and Histologic Healing after Coil Embolization in Elastase-Induced Aneurysms: A Retrospective Study

Abstract: BACKGROUND AND PURPOSE:There are, to our knowledge, no histologic data correlating aneurysm volume with histologic healing following coil embolization of aneurysms. We report a retrospective study comparing histologic outcome with aneurysm volume in elastase-induced aneurysms in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…We found a significant relationship between aneurysm volume and recurrence; as previously demonstrated, aneurysms with large volumes (>600 mm 3 ) had a higher incidence of recurrence than those with small volumes. Ding et al 18 analyzed data on aneurysm volume and histologic healing after coil embolization in a rabbit elastase induced aneurysm model. The authors showed that complete thrombus organization within the aneurysms cavity and endothelium lining the neointima across the neck occurred more frequently in smaller aneurysms than in larger aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant relationship between aneurysm volume and recurrence; as previously demonstrated, aneurysms with large volumes (>600 mm 3 ) had a higher incidence of recurrence than those with small volumes. Ding et al 18 analyzed data on aneurysm volume and histologic healing after coil embolization in a rabbit elastase induced aneurysm model. The authors showed that complete thrombus organization within the aneurysms cavity and endothelium lining the neointima across the neck occurred more frequently in smaller aneurysms than in larger aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Embolization of aneurysms was performed with platinum coils, as previously described, by the same author who created them ( 18 ). High rates of volumetric occlusion, typically defi ned as greater than 25%, have been associated not only with low recurrence rates clinically ( 19 ) but also with robust histologic healing in experimental aneurysm models ( 13 ). Conversely, low volumetric occlusion rates, less than 20%, are associated with frequent recanalization and poor healing.…”
Section: Molecular Imaging: Gene Expression In Healed Aneurysms Aftermentioning
confidence: 99%
“…In animal models ( 13 ) and in clinical practice ( 14 ), the durability of aneurysm occlusion is superior in densely packed aneurysms, as compared with loosely packed aneurysms. We hypothesized that experimental aneurysms could be used to probe, by using gene microarrays focused on proteins and other factors…”
Section: Embolization Proceduresmentioning
confidence: 99%
“…In the current study, we substantially enhanced the methodology compared with the prior study. First, we controlled packing density across groups, since previous reports have shown improved healing with higher packing density and poorer healing in the aneurysms with reduced packing densities 31. Second, we compared two methods of vitamin C medication delivery and confirmed that adequate levels were achieved.…”
Section: Discussionmentioning
confidence: 75%